2010
DOI: 10.1016/j.foodchem.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of some water-soluble aroma precursors in goat meat and their enrolment on flavour profile of goat meat

Abstract: a b s t r a c tSelected water-soluble precursors, including sugars, free amino acids and nucleotides, were quantified in raw and cooked goat meat, as a part of a study which the main aim was to better understand the aroma formation in goat meat. When compared with the same precursors in beef, lamb and chicken, levels in goat meat were generally similar, except for fructose and glycine, which were present at higher concentrations in goat meat. Fructose, glucose, IMP, and cysteine suffered the greatest losses du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 28 publications
5
95
2
Order By: Relevance
“…[2,10,31] The decreases in IMP, GMP, and Hx could result from both their migration from the meat into the broth and the thermal degradation of IMP to inosine during stewing. [32] The decrease in the IMP in the chicken meat during stewing were consistent with results in goat meat after cooking [33] and was accompanied by a remarkable increase in the IMP content in the chicken broth. [7] Rotola-Pukkila et al [11] have reported that IMP in pork meat remained constant after cooking at 80°C for 120 min.…”
Section: Changes In Faa Content With Different Stewing Timessupporting
confidence: 79%
See 1 more Smart Citation
“…[2,10,31] The decreases in IMP, GMP, and Hx could result from both their migration from the meat into the broth and the thermal degradation of IMP to inosine during stewing. [32] The decrease in the IMP in the chicken meat during stewing were consistent with results in goat meat after cooking [33] and was accompanied by a remarkable increase in the IMP content in the chicken broth. [7] Rotola-Pukkila et al [11] have reported that IMP in pork meat remained constant after cooking at 80°C for 120 min.…”
Section: Changes In Faa Content With Different Stewing Timessupporting
confidence: 79%
“…[33,36] The TAV of IMP was greater than 1 in both the raw and stewed meat samples (1, 2, and 3 h; Table 2). IMP was the most important flavor-providing 5′-nucleotide in meat and is known to impart a pleasant taste and contribute to the umami taste.…”
Section: Changes In Faa Content With Different Stewing Timesmentioning
confidence: 96%
“…An increase in WSN was observed when the temperature was increased. The composition of NPN in the crucian carp soup was the nitrogen of free amino acids, nucleotides, and peptides, which can directly contribute to the formation of flavour or as flavour precursors (Madruga et al 2010). In the present study, the content of NPN in soups also increased with the increase of cooking temperature.…”
Section: Sds-pagesupporting
confidence: 60%
“…Meat quality is the conjunct of acceptable sensory characteristics that are defined by product colour, tenderness, juiciness, flavour and aroma (Renerre 1981;Madruga et al 2010). The instrumental measurements in the present study indicated no difference in tenderness of LT steaks from the four Canadian beef quality grades at 6 to 8 d postmortem and after an additional 14-d aging.…”
Section: Discussionmentioning
confidence: 48%